Factors affecting the trends in evaporation during different crop growing seasons over India - SAMUI, R.P.; JOHN, G.; RANSURE, S.P.; PACHANKAR, M.A. (MAUSAM, 2011)
Evaporation, rainfall and meteorological data for the period 1971-2004 for 58 well distributed stations over India were selected for the study. Trends of evaporation and rainfall in five regions, viz., Northwest, North, Northeast, Central and Peninsular regions of India during different crop growing seasons, viz., kharif, rabi and summer and the meteorological factors contributing towards the trend were analyzed. Annual evaporation shows decreasing trend in all the regions of the country. Trends in seasonal evaporation during kharif, rabi and summer seasons also showed decreasing trends in Northwest, North, Central and Peninsular regions of the country while few locations in Northeast India, viz., Guwahati, Dibrugarh and Tocklai showed significant increasing trend in evaporation during kharif and rabi seasons. No significant trend in annual and seasonal rainfall was observed in Indian region except a few stations in peninsular India where increasing trend was observed. Normalized anomalies of maximum temperature, relative humidity and vapour pressure showed increasing trend in Northwest and Northern regions during all the three crop growing seasons while decreasing trend or no trend in wind velocity was observed in all the regions except in central region where increasing trend was observed during summer season. As evaporation relates to the meteorological elements, viz., temperature, sunshine duration, wind velocity and relative humidity, the likely causative meteorological factors for such changes are studied. Increasing trends in maximum temperature was observed in central and peninsular inland regions of the country during rabi and summer seasons while slight decreasing trends were observed in the Northeast region during kharif season. High positive correlation found between maximum temperature and wind velocity indicates that the trend in evaporation is mostly influenced by these two factors. Increase in humidity and decrease in bright sunshine hours were both important and found correlated with the decrease in evaporation.